2019
DOI: 10.4025/actascianimsci.v42i1.46828
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of yeast culture and direct-fed microbial on gut histology and serum components of broilers challenged with suboptimal diets under heat stress

Abstract: The use of antibiotics in feed for growth promotion has been restricted in many countries, thus it is of interest to investigate potential alternatives for enhancing growth performance in birds. An experiment was carried out to evaluate the concurrent use of prebiotic and probiotic on gut histology and some blood chemicals of broiler chickens during heat stress. A total of 144 day-old male Ross 308 broiler chicks were randomly divided into 3 treatments. The first treatment was a diluted diet including rice bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
1
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
(26 reference statements)
2
1
1
1
Order By: Relevance
“…As for the architecture of intestinal mucosa, we obtained results comparable to other studies in which villi, crypts, or both were positively influenced by yeast supplementation in diets for broilers [60][61][62]. The higher number of PAS positive mucin producers cells is related in the literature to a protective effects for the intestinal mucosa [63].…”
Section: Discussionsupporting
confidence: 85%
“…As for the architecture of intestinal mucosa, we obtained results comparable to other studies in which villi, crypts, or both were positively influenced by yeast supplementation in diets for broilers [60][61][62]. The higher number of PAS positive mucin producers cells is related in the literature to a protective effects for the intestinal mucosa [63].…”
Section: Discussionsupporting
confidence: 85%
“…Solanki et al (2020) and Syrovatko (2021) recorded non-significant effect on serum total protein, glucose and cholesterol due to supplementation of acidifier powder in broiler diets. In contrast to the present findings, Brzoska et al (2013) and Seifi et al (2015) observed significant difference of acidifier powder supplemented groups in blood glucose and cholesterol as compared to control group.…”
Section: Hemato-biochemical Parameterscontrasting
confidence: 99%
“…The present findings were similar with Taherpour and Ghasemi (2014) in broiler birds supplemented with a combination of prebiotic and acidifiers. However, Emami et al (2012) andSaheh et al (2014) found that adding prebiotic and Heidari et al (2018) and Seifi et al (2015) found that adding acidifier non-significant effect on body weight gain of broilers.…”
Section: Growth Performancementioning
confidence: 99%
“…The enhanced histomorphology of the jejunum in broilers fed TS diets may be ascribed to the stimulatory action of the product. Yeast present in TS diets may have improved the histoarchitecture of the intestine, which supports the findings of others [ 18 , 31 ]. This could be the main factor that explains the impact of dietary TS additive on growth indices during the finisher production phase, thereby enhancing the uptake of nutrients needed for body growth and development.…”
Section: Discussionsupporting
confidence: 89%